Drying characteristic of emulsified gelatin film - Abdullah, Saarwani (2017)
The purpose of this study are to determine drying characteristic of emulsifiededible film at different temperatures and to determine the optimumconditionfordrying. Nowadays, the application of the edible film is being increased. Therefore, theuses of the edible film are also increasing. The edible film is introduced as alternativeway to minimize the uses of synthetic polymer. It also can be eaten and degrade easily. The drying process is an important requirement in order for the filmto be usedasfood packaging. The drying characteristic can be described in drying kinetic model and optimum temperature that used for the film. The drying of films also an effectiveways of extending the shelf life by reducing the moisture content of the material that can reduced the microbial growth and enzymatic reaction. It is also involvedtheheat transfer from heating the medium to the product surface. The method used topreparethe film is by casting method. The film was dried at the different temperature whichare 45ºC, 50ºC, 55ºC and 60ºC. The material or chemicals that used to preparethefilm are plasticizer (glycerol), protein (gelatin), distilled water and lipids (vegetableoil) which is sunflower oil. The optimum temperature of emulsified gelatin film was 60ºC. When the drying time was increased, the moisture content was decreased. Lastly, Page model was the best fit model because R² was the highest, andlowerMBE and RMSE which were 0.9396, 0.0026 and 0.0515 respectively.